Research on timing method for single intersection in transportation Internet of things based on improved Webster algorithm - Lin MA; Fuyang CHEN; Bin JIANG (物联网学报)
Aiming at the timing signal problem of single intersection,a timing method based on the improved Webster algorithm in transportation Internet of things was proposed by combining the micro level analysis method with the macro level analysis method.In order to optimize the saturation and signal control delay,the average delay model was established.The game model and the conflict model were established with non-signal control and signal control.And the conflict analysis was carried out to illustrate that the optimal signal timing could coordinate the conflicting traffic flow.Based on the improved Webster algorithm,the shortest time required for the motor vehicle to pass the single intersection was additionally considered and a three-step optimization method for timing method at single intersection was proposed to reduce the traffic delay to ensure that the vehicle could pass effectively.The simulation results illustrate the effectiveness of the proposed solution.